2016
DOI: 10.1371/journal.pone.0167527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Two Monoclonal Antibodies against the Same Epitope on B-Cell Receptor Associated Protein 31

Abstract: Previously, we showed that B-cell receptor associated protein 31 (BAP31), an endoplasmic reticulum (ER) membrane chaperone, is also expressed on the cell surface by two monoclonal antibodies (MAbs) 297-D4 and 144-A8. Both MAbs recognize the same linear epitope on the C-terminal domain of BAP31, although they were independently established. Here, flow cytometric analysis showed that 144-A8 had additional binding properties to some cells, as compared to 297-D4. Quantitative antigen binding assays also showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The similar results were obtained with A549 sphere cells ( Fig 4D, 4E and 4F ). The same phenomenon was also obtained with hESCs where csBAP31 are expressed on the cell surface [ 6 8 ] ( S4 Fig ). Thus, the results suggest that enhanced cell surface expression of csBAP31 may contribute to apoptosis.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The similar results were obtained with A549 sphere cells ( Fig 4D, 4E and 4F ). The same phenomenon was also obtained with hESCs where csBAP31 are expressed on the cell surface [ 6 8 ] ( S4 Fig ). Thus, the results suggest that enhanced cell surface expression of csBAP31 may contribute to apoptosis.…”
Section: Resultssupporting
confidence: 72%
“…BAP31 is cleaved by caspase-8, and its cleaved product, p20, is an important inducer of apoptosis [ 4 , 5 ]. Although BAP31 is mainly localized to the ER membrane, recent studies have shown that BAP31 is also present on the cell surface of human embryonic stem cells (hESCs) [ 6 8 ]. It seems that cell surface BAP31 (csBAP31) promotes cell survival through the regulation of cell adhesion to extracellular matrix in hESCs [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%